The Effect Of Sustainable Development Goals And Fintech Adoption On Financial Reports Quality In Jordanian Islamic Banks - Mujahid Hamood Hilal AlZakwani; Murad Ali Ahmad Al-Zaqeba; Ammar Daher Bashatweh; Omima Al-refai; Khawla Kassed Abdo (Innovative Research Publishing, 2025)
Indexed Publication (Tier 2)